Media tacking to media transport using a media tacking belt - FLETCHER GERALD M; DE JONG JOANNES N. M; KNAUSDORF PETER J (2015)
When tacking print media to a print media transport belt in a printer, a tack module having a pair of nips is employed to control charge migration in across the print media in order to tolerate lead edge curl while ensuring uniform printing. An upstream nip is formed by a first bias transfer roll and a first backup roll, and a downstream nip is formed by a second bias transfer roll and a second backup roll. The respective backup rolls are offset slightly upstream of the respective bias transfer rolls. Charge of opposite polarities is applied to the first backup roll and the second bias transfer roll to facilitate taking of the print media to the print media transport belt.